Analisis Kesalahan Penulisan Kata Baku dalam Teks Laporan Hasil Observasi Siswa Sekolah Menengah Atas - Oktavian Yoga Pratama Yahya; Muslim Muslim (Lingua Franca, 2026)
Writing skills are one of the essential language competencies in Indonesian language learning because they are closely related to students’ critical, logical, and systematic thinking abilities. Through writing activities, students are not only expected to express their ideas in written form but also to organize their thoughts coherently and apply appropriate language rules according to academic contexts. This study employed a qualitative approach with a case study design aimed at analyzing the use of standard vocabulary in observation report texts written by tenth-grade students of SMAN 1 Kunto Darussalam, Rokan Hulu. The research data consisted of observation report texts with a sample of 30 students. Data were collected through documentation and observation, while data analysis involved identifying non-standard words and classifying errors based on affixation, reduplication, and compounding according to EBI sixth edition. The results showed that students still frequently used non-standard words influenced by everyday spoken language, limited understanding of standard spelling rules, and lack of structured writing practice. Therefore, continuous guidance is needed to improve students’ accuracy in using standard vocabulary.